Missed Tetralogy of Fallot in an Elderly Woman With a Known Ventricular Septal Defect - Kalra, Dinesh (CJC Open, 2020)
Tetralogy of Fallot is a congenital heart disease comprised of a tetrad of ventricular septal defect, pulmonary stenosis, overriding aorta, and right ventricular hypertrophy. In developed countries, most cases are diagnosed in babies; mortality is high if not surgically corrected in a timely manner. We describe herein a woman who was diagnosed at age 73 years. Several factors accounted for her unusual longevity. We highlight the importance of multimodal imaging to look for other associated anomalies of tetralogy of Fallot in cases of apparent simple ventricular septal defect when the echocardiographic images are either suggestive or suboptimal.